North Korea-Pakistan Relations and Technology Transfers - Abad, Gracia (UNISCI Discussion Papers, 2012)
North Korea may well constitute a threat for international peace and security not only for its nuclear weapons and missile programs but also due to the transfer of such know-how. In this regard, the relation between the North Korean State and Pakistan deserves special attention. Thus, the article will analyze the nuclear and missile exchanges between Pakistan and North Korea and the short, medium term implications of the North Korean transfers.
Keywords: North Korea; Pakistan; nuclear; weapons; missiles; Khan.